2022
DOI: 10.1111/codi.16454
|View full text |Cite
|
Sign up to set email alerts
|

Protective ileostomy creation after anterior resection of the rectum: Shared decision‐making or still subjective?

Abstract: Aim:The choice of whether to perform protective ileostomy (PI) after anterior resection (AR) is mainly guided by risk factors (RFs) responsible for the development of anastomotic leakage (AL). However, clear guidelines about PI creation are still lacking in the literature and this is often decided according to the surgeon's preferences, experiences or feelings. This qualitative study aims to investigate, by an open-ended question survey, the individual surgeon's decision-making process regarding PI creation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Our study also observed a signi cant reduction in need for intraoperative or postoperative blood transfusions for robotic patients when compared to laparoscopic patients. This result is consistent with the existing literature (23) and is of particular importance considering the negative impact of blood transfusions on colorectal cancer recurrence and mortality (24). It has been postulated that perioperative transfusions in cancer patients weaken the immune system permitting reduced cancer control.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also observed a signi cant reduction in need for intraoperative or postoperative blood transfusions for robotic patients when compared to laparoscopic patients. This result is consistent with the existing literature (23) and is of particular importance considering the negative impact of blood transfusions on colorectal cancer recurrence and mortality (24). It has been postulated that perioperative transfusions in cancer patients weaken the immune system permitting reduced cancer control.…”
Section: Discussionsupporting
confidence: 91%
“…Due to surgeon factor would affect surgical process [ 12 ], the same experienced surgical team at our center performed all procedures in order to eliminate bias caused by different experience. All surgeons have the same level of experiece.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps the most mitigating evidence against surgical technique as a cause of anastomotic leaks relates to the observation that even in high volume centers, when performed by expert high volume surgeons, leaks still occur, although at low rates [4]. The fact that use of the protective stoma continues to be advocated in selected cases also supports the notion that some leaks simply cannot be prevented [5,6 ▪ ]. Modifiable and actionable aspects among ‘patient-related factors’ include weight loss, smoking cessation, limiting blood loss and the application of enhanced recovery programs (ERPs).…”
Section: Introductionmentioning
confidence: 99%